The Role of Parents in Learning Motivation and Student Achievement: a good achievement: a good achievement - Ernawati, Ernawati (Saba Jaya Publisher, 2023)
This study formulates the problem, The Role of Parents in Learning Motivation and Student Achievement: a good achievement, So how does the influence of student achievement from the role of parents? and does parental motivation affect student achievement? The results of the study show that the participation of parents means that the progress and improvement of children's learning achievement and learning motivation at school can continue to increase, along with increasing age and children's reasoning power. The role of parents who teach and guide becomes an additional teaching outside of school for students in achieving their learning achievements. This study to collect data with literature sources.